Is hiring foreign worth it? Spillover from foreign firms' human capital and local firms' productivity - Ju Hyun Pyun; Jong-in Sun (Asian Development Bank Institute (ADBI), 2022)
This study examines the effect of foreign direct investment (FDI) on local firms' productivity via human capital transfer from MNEs to local firms. Using the firm-level data for 2010-2015 from the Republic of Korea, we identify human capital spillovers using local firms' hired permanent foreign employees in an industry and region where MNEs and local firms operate. This identification is valid because permanent foreign workers hired by local firms tend to be visa holders from MNEs due to the Republic of Korea's visa regulations. We find that the industry and regional FDI positively affect local firms' productivity, particularly firms with higher growth in hiring skilled foreign employees. This human capital spillover from FDI is also more pronounced in high R&D-intensive industries. Our results are robust with various measures of skilled foreign employees hired by local firms, variations of specifications, and controlling for endogeneity issues. Our findings on positive FDI spillovers via human capital transfer to a local firm suggest that policymakers may relax unnecessary regulations for highly skilled foreign workers and provide a platform where a local firm's manager and skilled foreign employees find each other.
Keywords: D24; F21; F23; J24; J63; O33; 330; FDI; firm productivity; human capital; foreign employees; technology spillover; knowledge spillover; visa status